1999
DOI: 10.1128/iai.67.5.2482-2490.1999
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Analysis of Secreted Aspartyl Proteinase Expression in Human Oral Candidiasis

Abstract: Secreted aspartyl proteinases are putative virulence factors inCandida infections. Candida albicans possesses at least nine members of a SAP gene family, all of which have been sequenced. Although the expression of the SAPgenes has been extensively characterized under laboratory growth conditions, no studies have analyzed in detail the in vivo expression of these proteinases in human oral colonization and infection. We have developed a reliable and sensitive procedure to detect C. albicans mRNA from whole sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
70
1
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(82 citation statements)
references
References 54 publications
(64 reference statements)
7
70
1
2
Order By: Relevance
“…In general, Sap2 is the main C. albicans proteinase. 5,9,10 Our results are consistent with the premise that Sap2 is a predominant proteinase of C. albicans, as SAP2 expression was observed in all patients with VVC, RVVC and all Candida carrier individuals ( Table 2). In support of this conclusion is the broad substrate specificity of Sap2, 2 and its role in causing tissue damage as assessed in an reconstituted human epithelium (RHE) oral model 6 and virulence in a rat vaginitis model.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In general, Sap2 is the main C. albicans proteinase. 5,9,10 Our results are consistent with the premise that Sap2 is a predominant proteinase of C. albicans, as SAP2 expression was observed in all patients with VVC, RVVC and all Candida carrier individuals ( Table 2). In support of this conclusion is the broad substrate specificity of Sap2, 2 and its role in causing tissue damage as assessed in an reconstituted human epithelium (RHE) oral model 6 and virulence in a rat vaginitis model.…”
Section: Discussionsupporting
confidence: 89%
“…An RT-PCR was used for analysis of SAP1 to SAP7 gene expression in vivo infection as described elsewhere. 9 Nine RT-PCRs were performed for each sample of RNA isolated from each patient vaginal secretion sample. These included the five experimental reactions for SAP detection (SAP1, SAP2, SAP3, SAP4-6, and SAP7) and four different control reactions, as follows: two actin control reactions to demonstrate the presence or absence of Candida species, a negative (water) control reaction, and a positive control reaction carried out by using total RNA isolated from SAP2 mRNA-expressing C. albicans ATCC 14053 cells (SAP2 RNA).…”
Section: Rt-pcr Analysis Of C Albicans Saps Mrna Expression In Clinimentioning
confidence: 99%
See 1 more Smart Citation
“…The first in vivo study detecting C. albicans mRNA from whole saliva of patients with oral C. albicans infection indicated that the pathogenesis of Candida-associated DS may be associated with the differential expression of individual SAP genes. 38 Furthermore, the significant differences in SAP activity between C. albicans strain isolates from diseased and healthy patients suggested a correlation between in vitro biofilm-associated proteinase activity and severity of disease. 28 However, given the clinical spectrum of disease for patients with DS, the salivary flow or presence of biofilm alone does not explain the clinical presentation, since it is clear that host immune factors are likely to play a role in the pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…4 Proteinase specificity acts as a key factor in the degradation and invasion of the host, and it is important to destroy the main defense barriers of the oral mucosa. 5 The pathogenesis of EC by C. albicans is associated with its capability to produce exoenzymes, such as proteinase and phospholipase. 6 Proteinase and phospholipase production facilitates yeast adherence and invasion of the mucosa.…”
Section: Introductionmentioning
confidence: 99%